2005
DOI: 10.1021/ie040214f
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel from Used Frying Oil. Variables Affecting the Yields and Characteristics of the Biodiesel

Abstract: A study was performed of the transesterification reaction of used frying oil by means of methanol, using sodium hydroxide, potassium hydroxide, sodium methoxide, and potassium methoxide as catalysts. The objective of the work was to characterize the methyl esters for use as biodiesels in compression ignition motors. The operation variables used were methanol/oil molar ratio (3:1−9:1), catalyst concentration (0.1−1.5 wt %), temperature (25−65 °C), and catalyst type. Also, experiments in two stages of reaction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
180
1
9

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 441 publications
(222 citation statements)
references
References 33 publications
13
180
1
9
Order By: Relevance
“…Therefore EU banned the use of waste cooking oils in the composition of animal feed in 2002. Most of the toxic compounds in the waste cooking oil are oxidation products from fatty acids, especially from polyunsaturated fatty acids [5], [6]. Manuscript application of Fourier transform infrared (FTIR) spectroscopy has increased in food studies, and particularly has become a powerful analytical tool in the study of edible oils and fats.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore EU banned the use of waste cooking oils in the composition of animal feed in 2002. Most of the toxic compounds in the waste cooking oil are oxidation products from fatty acids, especially from polyunsaturated fatty acids [5], [6]. Manuscript application of Fourier transform infrared (FTIR) spectroscopy has increased in food studies, and particularly has become a powerful analytical tool in the study of edible oils and fats.…”
Section: Introductionmentioning
confidence: 99%
“…Since the prices of edible vegetable oils, e.g. soybean oil, are higher than that of diesel fuel, waste vegetable oils (Encinar, et al, 2005;Felizardo, et al, 2006;Dorado, et al, 2002;Cetinkaya and Karaosmanolu, 2004) and non-edible crude vegetable oils as Jatropha, Pongamia pinnata (Karmee and Chadha, 2005) and tigernut oil (Ugheoke, et al, 2007) have been intensively investigated as potential low priced biodiesel sources. Biodiesel made from these feedstocks was predicted to be more economical than the biodiesel produced from refined vegetable oil.…”
Section: Introductionmentioning
confidence: 99%
“…Alkyl oxide solutions of sodium methoxide or potassium methoxide in methanol, which are now commercially available, are the preferred catalysts for large continuous-flow production processes (Singh, et al, 2006). Biodiesel with the best properties was obtained using potassium hydroxide as catalyst in many studies (Encinar, et al, 2005;Jeong and Park, 1996;Karmee, 2005;Dorado, et al, 2004;Dorado, et al, 2002;Darnoko and Cheryman, 2000;Ugheoke, et al, 2007;El-Mashad, et al, 2006). Besides, many other studies achieved best results using NaOH (Felizardo, et al, 2006;Vicente, et al, 2004;Cheng, et al, 2004;de Oliveira, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With further increase in molar ratio the conversion efficiency more or less remains the same but the energy required for the recovery of methanol becomes higher. It was concluded that the use of waste cooking oils is an effective way to reduce the cost of biodiesel production 5 . The advantages of using waste cooking oils to produce biodiesel are the low cost and prevention of environment pollution.…”
Section: Introductionmentioning
confidence: 99%